Заболеваемость лимфо и ретикулосаркомами взрослого населения Украины в 1991–1998 гг. - Кривец, Д.Я. (Онкологія, 2000)
Изучены особенности заболеваемости лимфо- и ретикулосаркомами (С82–С85) взрослого (25 лет — 54 года) населения Украины в 1991–1998 гг. На основе данных о случаях заболевания и возрастно-половом составе населения областей Украины, АР Крым и г. Киева рассчитаны показатели заболеваемости на 100 000 населения, вычислены их дисперсия и среднее квадратическое отклонение. Выявлена тенденция к cнижению заболеваемости гемобластозами данной формы на изучаемой территории в 1991–1998 гг. Изучены географические особенности и составлены карты заболеваемости лимфо- и ретикулосаркомами мужского и женского населения Украины в 1991–1998 гг. The aim of the work was to study the incidence of the lympho- and reticulosarcomas in adult (25–54 years) population of Ukraine in 1991–1998. The incidence per 100 000 population with respective variance and the standard deviation have been calculated on the basis of the official statistical data reporting the number of the cases as well as the age and sex structure of the population in the regiones of Ukraine, the Crimea Republic, and Kyiv. According to the official data the incidence of hemoblastoses under study in 1991–1998 in the regions being analyzed has a tendency to decrease. The geographic patterns have also been studied and the maps picturing the incidence of the lympho- and reticulosarcomas in 1991–1998 in mail and femail populations of Ukraine have been presented.